Elemen Pembentuk Sense of Place Taman Nostalgia sebagai Ruang Terbuka Publik Kota Kupang - Yulia Isadora Alvita Gon; Robertus Mas Rayawulam; Yuliana Bhara Mberu; Reginaldo Christophori Lake; Pilipus Jeraman (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2023)
Title: Elements Forming the Sense of Place of Taman Nostalgia as a Public Open Space in the City of Kupang This research aims to identify the elements that form the sense of place in Taman Nostalgia as a green open space in Kupang. Sense of place is a psychological phenomenon that affects users' perceptions and relationships with their environment. Shamai's theory is used as the basis for the conceptual framework, which is then operationalized through interview and questionnaire methods as data collection tools. This study involves active participants, namely visitors to Taman Nostalgia. In-depth interviews are conducted to gain a detailed understanding of individual visitors' experiences with Taman Nostalgia, while the questionnaire is used to obtain broader data from visitors. The research findings indicate that the sense of place in Taman Nostalgia is strengthened by the presence of the Gong Perdamaian Nasional as one of the significant physical elements. Other relevant elements include architectural design, vegetation, and cultural elements, which also contribute to forming the sense of place. The implications of these findings can be used as a basis for the development and planning of public green open spaces, considering the elements that enhance users' emotional relationships with the urban environment.